Strategi Komunikasi Guru dalam Menyampaikan Pesan Pembelajaran Kepada Anak Usia Dini (Studi Kasus TK Ar-Rahman Kecamatan Tanjung Karang Barat Kota Bandar Lampung) - Afrina Syafriyanti; Sri Choiriyati; Mike Meiranti (CV. ITTC INDONESIA, 2026)
This study was motivated by the fact that some early childhood students at TK Ar-Rahman, Tanjung Karang Barat District, Bandar Lampung City, still experienced difficulties in understanding learning messages, requiring teachers to repeat instructions during the learning process. This study aimed to describe teachers' communication strategies in delivering learning messages to early childhood students. The research employed a qualitative method with a case study approach. Data were collected through observations, interviews, and documentation involving one principal and five teachers as informants. Data were analyzed using the Miles and Huberman interactive model, including data collection, data reduction, data display, and conclusion drawing. The findings revealed that teachers implemented communication strategies by understanding students' characteristics, organizing messages using simple language, applying various teaching methods such as storytelling, games, singing, demonstrations, and question-and-answer sessions, and utilizing attractive learning media. Based on David K. Berlo's SMCR communication model, the communication process fulfilled the elements of source, message, channel, and receiver, enabling students to understand learning messages through attention, responses, the ability to follow instructions, and active participation in classroom activities. Therefore, teachers' communication strategies play an important role in creating an effective learning process.